2015
DOI: 10.5539/jel.v4n4p39
|View full text |Cite
|
Sign up to set email alerts
|

Case Studies for Enhancing Student Engagement and Active Learning in Software V&V Education

Abstract: Two critical problems facing the software (S/W) industry today are the lack of appreciation of the full benefits that can be derived from Software Verification and Validation (V&V) and an associated problem of shortage of adequately trained V&V practitioners. To address this situation, the software V&V course curriculum at the author's institution is being improved via a National Science Foundation (NSF)-funded project. The basic objectives of this project are to enhance the quality of software education via i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 9 publications
1
11
0
Order By: Relevance
“…Specifically, they help students develop problem-solving, critical-reasoning, and analytical skills, all of which are valuable tools that prepare students to make better decisions and become better students and, ultimately, better employees. The results from this work has recently been reported in journals 5,15 .…”
Section: Interdisciplinary Educational Innovationssupporting
confidence: 57%
See 1 more Smart Citation
“…Specifically, they help students develop problem-solving, critical-reasoning, and analytical skills, all of which are valuable tools that prepare students to make better decisions and become better students and, ultimately, better employees. The results from this work has recently been reported in journals 5,15 .…”
Section: Interdisciplinary Educational Innovationssupporting
confidence: 57%
“…The work is then disseminated through professional societies like ASEE, Frontiers in Education (FIE) conference sessions or workshops or through campus based workshops 5 . This knowledge transmission model has limited effectiveness because of its one-shot, one-size-fits-all, just-in-case training approach fails to address local difference and needs 6 .…”
Section: Introductionmentioning
confidence: 99%
“…In our work, we have modeled the N N → Y N interaction by the one meson exchange effect, with the |∆S| = 1 interactions calculated using the vacuum saturation approximation. The glunoic correction to the CP-odd meson-baryon interaction generated by a CP-odd four-quark interaction is typically O(100%) in the large N c analysis [120][121][122]. In the case of |∆S| = 1 processes, however, we have a strange quark which forbids the exchange of quarks between mesons and baryons, reducing higher order gluonic corrections.…”
Section: Results and Analysismentioning
confidence: 99%
“…Raju and Sankar (1999) define Case Study education as providing students with a record of a technical and/or business issue that actually has been faced by managers, together with surrounding facts, opinions, and prejudices upon which management decisions have to depend. In this project, Case Studies are drawn from a wide range of industry SV&V practices and reported in detail elsewhere (Manohar et al, 2015). Students are presented industry standard documents for review to prepare for the tasks.…”
Section: Case Studiesmentioning
confidence: 99%